OPTIMIZATION OF PID TUNING USING GENETIC ALGORITHM - Tengku Ahmad Faris, Ku Yusoff (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Controller tuning is one of the important aspect in industry. With a good tuning method, it can ensure the quality of the process and product produce. Apart from that, it can protect the environment and help the company to reduce the cost. Genetic algorithm is one of the tuning method that increase usage and awareness in industry. By comparing the method with the conventional tuning method, the performance of tuning method by using genetic algorithm can be seen.